LANDSCAPE THEORY IN GEOGRAPHY - (:unkn) unknown (MARMARA UNIV, 2018)
In this study, we will try to explain what landscape is and its theoretical framework. Landscape is widely being used in geography especially in cultural geography. Like every concept landscape has transformed as it takes on new meanings and loses some at the same time. There is a close connection between the emerging new meanings and dominating approach, paradigm and theories in a discipline. In general, every emerging approach or paradigm can affect and transform related concepts in a given discipline. Therefore, it is proper to use concepts and terms in their context. From 15th century onwards, landscape has been used in different contexts in different disciplines in different ways. For this reason, landscape will be treated from different approaches, meanings and theories like cultural landscape, quantitative revolution, feminist theory, Marxist and radical geography, humanistic geography, postmodern and poststructuralist approaches, non-representational theory and actor-network theory.
Keywords: Landscape; Geographical Paradigms; Cultural Geography; Power Relations